Chemical Profile and Antioxidant Properties of Extracts and Essential Oils from Citrus × limon (L.) Burm. cv. Femminello Comune. Issue 5 (May 2016) - Loizzo, Monica Rosa; Tundis, Rosa; Bonesi, Marco; Sanzo, Giuseppe Di; Verardi, Alessandra; Lopresto, Catia Giovanna; Pugliese, Alessandro; Menichini, Francesco; Balducchi, Roberto; Calabrò, Vincenza
Abstract : Citrus × limon cv. Femminello Comune (Rutaceae) from Rocca Imperiale (Italy), one of the six Protected Geographical Indication (PGI) Italian lemon crops, has been recently received renewed interest. In this work, fresh and dried peels and leaves were extracted by hydrodistillation, supercritical fluid extraction (SFE), and Soxhlet apparatus. Chemical profile was assessed by gas chromatography (GC) and gas chromatography/mass spectrometry (GC/MS). Except for leaves extracts obtained by Soxhlet apparatus, the monoterpene hydrocarbons fraction dominated. Limonene, γ ‐terpinene, and β ‐pinene were the main identified compounds. The antioxidant activity was investigated using different in vitro assays namely 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH), ABTS, ferric reducing ability power (FRAP), and β ‐carotene bleaching test. In DPPH test, the essential oil obtained by hydrodistillation of fresh peel exhibited the highest activity ( IC 50 of 1.17 mg/ml). Leaves extracted by SFE showed a good activity in both DPPH and β ‐carotene bleaching test with IC 50 values of 2.20 and 6.66 mg/ml, respectively. Monoterpene hydrocarbons fraction exhibited a positive Pearson 's correlation coefficient with all antioxidant assays. Leaves, often considered waste material, should be considered from a different point because they represent a matrix of indisputable interest. Abstract :